Analysis of Junior High School Students’ Learning Styles as the Basis for Developing a Differentiated Science E-Module - Yandri Alfret Dooh; Raharjo; Elok Sudibyo; Muhammad Satriawan; Maharani Agustina Arivi (Universitas Syiah Kuala, 2026)
This study aims to analyze the learning style profiles of ninth grade students at SMP Negeri 1 Kupang and to examine their implications for the development of differentiated, technology based science e-modules. A quantitative descriptive approach was employed involving 344 students from eleven classes. Data were collected using a VAK (visual, auditory, kinesthetic) learning style questionnaire and analyzed using percentage distributions and the Simpson diversity index to describe classroom heterogeneity. The results revealed that students learning styles were relatively balanced, with an average proportion of 32.9% visual, 30.7% auditory, and 36.4% kinesthetic learners. The diversity index across classes ranged from 0.49 to 0.67, with an average of 0.65, indicating a moderate to high level of heterogeneity in learning style preferences within classrooms. While several classes showed balanced distributions, one class was dominated by kinesthetic learners, highlighting variations in instructional needs among classes. These findings suggest that science learning at the junior high school level should not rely on uniform instructional strategies, but instead adopt differentiated and multimodal approaches that can accommodate diverse learning preferences. The identified learning style profiles provide an empirical basis for designing interactive and differentiated science e-modules that integrate visual, auditory, and kinesthetic learning pathways. Such e-modules are expected to support student engagement, autonomy, and conceptual understanding, and to foster more inclusive and student centered science learning in line with current curriculum demands.